Serum Bilirubin and GGlutamyl Transferase in Female PatientsSuffering from Migraine (Medical Forum Monthly, 2021)
Objective: To analyze serum bilirubin and liver aminotransferase in migraine female patients at a tertiary care hospital of Sindh.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Isra University Hospitals from February 2019 to January 2020.Materials and Methods: A sample of 100 diagnosed cases of migraine and 100 controls was selected according criteria. Severity of migraine headache was defined according to the Visual Analogue Scale (VAS). 5 ml blood was drawn; 2 ml was put in EDTA bottles for blood parameters and 3 ml was centrifuged to get sera for detection of liver function tests. Data was analyzed on statistical software SPSS (ver 21.0) by Student t-test (at P ≤ 0.05) and correlation by Spearman`s rho testing.Results: Total, Direct and Indirect bilirubin in control and migraine patients were noted as 1.24±0.09 and 1.07±0.08 mg/dl (P=0.0001), 0.86±0.09 and 0.71±0.04 mg/dl (P=0.0001), 0.27±0.08 and 0.23±0.09 mg/dl (P=0.001) respectively. GGT in control was 36.3±6.09IU compared to migraine patients as 44.9±8.3 IU. Total bilirubin, direct and indirect bilirubin reveals negative correlation with migraine severity, while gamma glutamyl transferase (GGT) reveals positive correlation.Conclusion: The present prospective study found low serum bilirubin and raised gamma – glutamyl transferase levels in migraine patients.